Solar refrigeration: evaluation of technical options and design of a solar-generator-adsorber for a novel adsorption refrigerator - Tabassum, Salim Abid (Cranfield University, 1989)
Various technical options for developing a solar operated refrigerator have been discussed. Their suitability for being used as a vaccine store for the conditions specified by the World Health (EPI) Organization Expanded Programme on Immunization 4have been evaluated. A model to predict the performance of a photovoltaic refrigerator have been developed and used to identify factors which influence its performance. It was concluded that it can be more competitive in areas where insolation is high and sunshine hours are long. It has been proposed that ice-lined refrigerators, which would run during the day, may be more economical and eliminate the need for a battery storage. The option of operating an 'Electrolux' absorption refrigerator with evacuated tube heat pipe collectors has been assessed. It was concluded that the operation was not possible without a major re-design of the commercially available models. However, it was proposed that coordination of the EPI with other development programmes may be useful. It is proposed to build, with this coordinated effort, biogas plants. Biogas can then fuel the modified burner of the kerosene fueled absorption refrigerators. This may well prove to be a cheaper option. Characterization of various adsorption pairs has been done using the experimental rig developed for the purpose. The influence of various properties of adsorption pairs on the performance of an adsorption refrigeration cycle has been studied. It was observed that the generation temperature in an adsorption refrigeration cycle (or a bivariant absorption system), for a specified operating regime, was only a function of the refrigerant. A relationship between the refrigerant properties and the generating temperature for specified operating conditions was developed. Using this relationship it was established that ammonia and methanol cannot be generated at temperatures below 1200C for WHO/EPI specified operating conditions, if the condenser was air-cooled. A novel idea of direct absorption of solar radiation into the activated carbon bed is put forward to combat the temperature differential of 214°C, in a conventional design of SGA, between the carbon and the metal container. The idea was practically implemented by replacing the top of the metal box by transparent glass sheet. The seal between the metal container and glass imposed practical difficulties in that design but the tests proved that the idea had potential. A new tubular design of the SGA is proposed finally which is hoped to bring improvement to the performance of activated carbon adsorption refrigerators.